Take Your Time to Grow: A Field Experiment on the Hiring of Youths - Dorothea Kübler; Julia Schmid; Robert Stüber (German Economic Review, 2019)
We investigate the effect of spells of no formal employment of young Germans on their chances of entering the labor market through an apprenticeship. We also study whether the potential negative effects of such spells can be mitigated by publicly provided training measures. In a field experiment, the fictitious applications of three young women were sent to firms advertising apprenticeships for the position of office manager. One application was from a fresh school-leaver and two from applicants who had been out of school for two years, where one of them had participated in a training measure. We find that applicants who have been out of school for two years and have participated in the training are more successful than older applicants without additional training. We do not find a significant difference between older applicants with or without training and fresh school leavers. Our findings show that training measures increase the attractiveness of applicants and that the potential stigma of spells of no formal employment after school are compensated by informal work experience or age or a combination of both.
Keywords: I28; J64; C93; 330; field experiment; apprenticeship; hiring decisions; informal and formal employment; training